Transmission of ST8-USA300 Latin American Variant methicillin-resistant Staphylococcus aureus on a neonatal intensive care unit: recurrent skin and soft- tissue infections as a marker for epidemic community-associated-MRSA colonization - Nurjadi, Dennis; Klein, Sabrina; Zimmermann, Stefan; Heeg, Klaus; Zanger, Philipp (Infection control and hospital epidemiology, 2017)
We report a mother-to-newborn transmission of ST8-USA300 Latin American Variant methicillin-resistant Staphylococcus aureus (MRSA) on a neonatal intensive care unit during kangaroo mother care in a German University Hospital, which raises the question of whether recurrent skin and soft-tissue infection (SSTI) is an important marker for colonization with epidemic MRSA clones.